Brown Bowel Syndrome: An Exceedingly Rare Condition with Longstanding Malabsorption and an Unusual Cause of Colon Pseudo-Obstruction - Adnan Alkurdi (Karger Publishers, 2021)
Brown bowel syndrome (BBS) is an exceedingly rare condition usually associated with longstanding malabsorption of any etiology. As a result of vitamin E deficiency and subsequent mitochondrial degeneration due to oxidative stress induced by free radicals, lipofuscin granules accumulate in the smooth muscles of the gastrointestinal tract resulting in myopathy and dysmotility with underlying disease aggravation. The current study reports a BBS case in a 64-year-old female patient who had undergone jejunoileal bypass surgery as a bariatric procedure. The patient was admitted with signs of malabsorption and ileus in computed tomography imaging. Endoscopic workup revealed no stenosis or obstruction. The colon histologically showed periodic acid-Schiff-positive lipofuscin granules in the lamina muscularis mucosa consistent with BBS. The vitamin E level in the patient was extremely low. Moreover, clinical improvement was documented following high-dose substitution. BBS should be considered in patients with malabsorption of any cause especially with signs of gastrointestinal dysmotility. Vitamin E substitution may improve clinical status and prevent further deterioration.